Improvement of biocontrol efficacy of Stenotrophomonas rhizophila strain pstu-hort-14 with sodium bicarbonate and lemongrass extract to control anthracnose of mango: Enhanced biocontrol of mango anthracnose using sodium bicarbonate - Uddin, M J; Robbani, M; Hasan, M F; Mehedi, M N H; Tanjila, U R; Islam, S M (Bangladesh Journal of Agriculture, 2025)
The study was conducted at the Postharvest and Plant Biotechnology Laboratory, Department of Horticulture, Patuakhali Science and Technology University, Patuakhali, Bangladesh during the period from July to December 2017 to test the potential of sodium bicarbonate and lemongrass extract to increase the biocontrol efficacy of Stenotrophomonas rhizophilla strain PSTU-Hort-14. All treatments were arranged in a completely randomized design (CRD) with replications and repeated twice. This bacterium was found to be highly compatible with 20% lemongrass extract and 2% sodium bicarbonate (SBC) or mixture of both. Both of these have suppressive activity against Colletotrichum gloeosporioides of mango and could be used as enhancer for biocontrol efficacy of PSTU-Hort-14 during mango storage. The survival and proliferation of PSTU-Hort-14 in mango wounds and on fruit surfaces was not affected by lemongrass extract and SBC throughout the storage period. In addition, PSTU-Hort-14 strain was able to colonize and multiply on the surface of mango fruits. The combination of PSTU-Hort-14 with lemongrass extract and SBC was more effective in controlling the anthracnose disease than PSTU-Hort-14 alone or other treatments including fungicide Dipheniconazol® both in inoculated or naturally infected fruits stored at 12±1ºC and 90±5% RH for 18 and 14 days, respectively. However, this combination offered a greater control by reducing 98.2% of the disease over control in naturally infected fruits at the end of 14 days storage at 12±1ºC and 90±5% RH and six days post ripening at 28 ± 2ºC, which was superior to that found with Dipheniconazol® or other treatments tested. Bangladesh J. Agri. 2025, 50(1): 47-63